2011
DOI: 10.1128/aem.05683-11
|View full text |Cite
|
Sign up to set email alerts
|

rnr Gene from the Antarctic Bacterium Pseudomonas syringae Lz4W, Encoding a Psychrophilic RNase R

Abstract: RNase R is a highly processive, hydrolytic 3-5 exoribonuclease belonging to the RNB/RNR superfamily which plays significant roles in RNA metabolism in bacteria. The enzyme was observed to be essential for growth of the psychrophilic Antarctic bacterium Pseudomonas syringae Lz4W at a low temperature. We present results here pertaining to the biochemical properties of RNase R and the RNase R-encoding gene (rnr) locus from this bacterium. By cloning and expressing a His 6 -tagged form of the P. syringae RNase R (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…The psrnr gene was seen to be 2313 bp in length (GenBank accession numbers MK624989) and to encode a protein with 770 amino acids, while the length of the rnr gene from Pseudomonas syringae Lz4W was seen to be 2658 bp, encoding 885 amino acids [12]. Based on sequence alignments with the related RNase Rs, the residues (Thr 646, Phe 654, Leu 665 and His 667) were identified as the catalytic sites in the sequence of PsRNR (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The psrnr gene was seen to be 2313 bp in length (GenBank accession numbers MK624989) and to encode a protein with 770 amino acids, while the length of the rnr gene from Pseudomonas syringae Lz4W was seen to be 2658 bp, encoding 885 amino acids [12]. Based on sequence alignments with the related RNase Rs, the residues (Thr 646, Phe 654, Leu 665 and His 667) were identified as the catalytic sites in the sequence of PsRNR (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…A growing number of evidence has indicated that RNase R is a cold shock protein (CspA), and its expression regulation is closely related to microbial adaptation [10,11]. It is well-known that the recruitment of RNase R to the degradosome complex is related to its need for low temperatures during growth [12]. It has been discovered that RNase R in Pseudomonas syringae plays an important role in growth at low temperature [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This Gram-negative nonfluorescent pseudomonad was isolated from soil samples from the Schirmacher Oasis and Antarctica (6). Our studies have yielded novel insights into various mechanisms of psychrophilic adaptation that include modifications in lipopolysaccharides (7, 8), the RecBCD complex (9, 10, 11), RNA polymerase (12, 13), and a novel RNA degradosome with exoribonuclease RNase R (14, 15, 16). We and others have generated a transposon-mutagenized library of cold-sensitive mutants which do not grow at 4°C but grow at 22°C, and their suppressors, for characterization of essential genes for growth at low temperatures (9, 17; M. K. Ray, unpublished results).…”
Section: Genome Announcementmentioning
confidence: 99%
“…It exhibited defects in the degradation of regulatory transfer-messenger RNA (tmRNA) suggesting that it plays a role in the turnover of tmRNAs (Purusharth et al, 2007;Sulthana et al, 2011). Decreased protein synthesis at 4°C in rnr mutants indicated that the accumulation of unprocessed 16S rRNAs in polysomes affects the protein translation machinery at the low temperature and cause cell death at 4°C (Purusharth et al, 2007;Sulthana et al, 2011) (Fig.3a). Ribosomal RNAs and tmRNAs possess different secondary structured elements, including hairpin duplexes and pseudoknots.…”
Section: Rna Metabolism-and Rna-degradation Machinerymentioning
confidence: 99%